Pengembangan Usaha Budidaya Lele Sebagai Upaya Pengentasan Stunting Rumah Tangga Di Kawasan Pedesaan - Dewi Laras Ati, Henny; Sukarson, Ardian; Luqmanul Hakim , Ikhsan; Syaifudin, Ahmad; Aditama Putra, Nico; Apriadi, Eko Aziz (CV. Tripe Konsultan, 2024)
This study aims to analyze the potential of developing catfish farming as an effort to alleviate stunting in rural areas, focusing on Jati Agung, South Lampung. The farming program led by Iwan Haryadi, A.Md., involved training on farming techniques, from pond preparation to feed management and harvesting. The results show that catfish farming not only provides economic benefits for farmers but also plays a crucial role in increasing household protein intake, which directly helps prevent stunting in children. Although challenges such as fluctuating feed prices and limited market access exist, with proper support, this farming initiative can further develop and significantly contribute to the well-being of rural communities.